2016
DOI: 10.3109/09513590.2015.1126818
|View full text |Cite
|
Sign up to set email alerts
|

SORCS1 polymorphism and insulin secretion in obese women with polycystic ovary syndrome

Abstract: We investigated the influence of SORCS1 polymorphisms on insulin secretion in obese women with PCOS. Metabolic status was recorded in 50 clinically well characterized PCOS patients. Oral glucose tolerance test was performed and laboratory parameters of insulin resistance measured. All patients were genotyped for SORCS1 rs1358030, rs1416406 and rs11192966 polymorphisms. Statistical analysis was performed using the Mann-Whitney test. SORCS1 rs1416406 significantly influenced stimulated glucose plasma levels (p =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…In our work, SORCS1 were negatively regulated by mir-335 and CNGA3 was negatively regulated by mir-182 and mir-19b-2 (Fig 3). SORCS1 encodes sortilin related VPS10 domain containing receptor 1,is associated with the Alzheimer's disease, type 2 diabetes and obese women with polycystic ovary syndrome[3840]. CNGA3 encodes cyclic nucleotide gated channel alpha 3, a member of cyclic nucleotide-gated cation channel protein family, is required for normal vision.…”
Section: Discussionmentioning
confidence: 99%
“…In our work, SORCS1 were negatively regulated by mir-335 and CNGA3 was negatively regulated by mir-182 and mir-19b-2 (Fig 3). SORCS1 encodes sortilin related VPS10 domain containing receptor 1,is associated with the Alzheimer's disease, type 2 diabetes and obese women with polycystic ovary syndrome[3840]. CNGA3 encodes cyclic nucleotide gated channel alpha 3, a member of cyclic nucleotide-gated cation channel protein family, is required for normal vision.…”
Section: Discussionmentioning
confidence: 99%
“…VCAM1 [1232], AQP8 [1233], FABP4 [1234], FABP5 [1235], BMP4 [1236], PRL (prolactin) [960], WNT5A [1237], ADAMTS9 [1238], NDNF (neuron derived neurotrophic factor) [1239], LHCGR (luteinizing hormone/choriogonadotropin receptor) [1240], LDLR (low density lipoprotein receptor) [1241], CD4 [1242], ADAMTS5 [1243], MAP2K6 [1244], ADAMTS1 [1245], PDE4B [1246], TH (tyrosine hydroxylase) [1247], MMP8 [1248], ADRB2 [969], KL (klotho) [1249], EPHA7 [1250], UCN2 [1251], CYP1A1 [970], LEPR (leptin receptor) [1252], IL15 [1253], BMP2 [1254], APOE (apolipoprotein E) [1255], CASP1 [1256], ACE (angiotensin I converting enzyme) [1257], PGR (progesterone receptor) [1258], GREM2 [1259], SORCS1 [1260], HKDC1 [1261], FADS1 [1262], S100A4 [1263], IL33 [1243], NGF (nerve growth factor) [1264], COMP (cartilage oligomeric matrix protein) [1265], FST (follistatin) [1266], GATA6 [1267], ACAN (aggrecan) [1268], AKR1C3 [1269], BDNF (brain derived neurotrophic factor) [1270], ANGPTL4 [1271], NOX4 [1272], VDR (vitamin D receptor) [1273], GPC4 [1274], TLR2 [1275], IL6 [1276], IGFBP3 [1277], TNIK (TRAF2 and NCK interacting kinase) [1278], APLN (apelin) [1279], PGF (placental growth factor) [1280], NRG1 [1281], LIF (LIF interleukin 6 family cytokine) [1282], ANGPTL1 [1283], KISS1 [1284], SORBS1 [1285] and TRH (thyrotropin releasing hormone) [1286] are a potential targets for polycystic ovarian syndrome. VCAM1 [1287], STRA6 [1288], AQP8 [1289], FABP4 [1290], SOX6 [1291], RAMP3 [1292], MMP12 [1293], FAIM2 […”
Section: Discussionmentioning
confidence: 99%
“…Özcan et al [526], Emokpae et al [527], Batista et al [528], Darbari et al [529], ElAlfy et al [530], Hounkpe et al [531], Vogel et al [532], Afifi et al [533], Shmukler et al [534], El Sissy et al [535], Cavalcante et al [536], Sadler et al [537], Kalai et al [538], Silva et al [539], Jhun et al [540] and Cai et al [541] that ALB (albumin), LPL (lipoprotein lipase), KL (klotho), UGT2B7, IFNG (interferon gamma), MPO (myeloperoxidase), BTK (Bruton tyrosine kinase), CD209, KCNN4, CCR5, TNF (tumor necrosis factor), CCR2, CCL5, NOS3, S100B and HBB (hemoglobin subunit beta) are associated with progression of sickle cell disease. Studies showed that altered expression of MTNR1A [542], GATA6 [543], EGF (epidermal growth factor) [544], LPL (lipoprotein lipase) [545], PPARGC1A [546], ERBB4 [547], KL (klotho) [548], GCLC (glutamate-cysteine ligase catalytic subunit) [549], NOX4 [550], SORCS1 [551], FKBP5 [552], CCNL1 [553], USP25 [554], SAA1 [555], MPO (myeloperoxidase) [556], GATA1 [557], LCN2 [558], IL1RN [559], IL11 [560], PDCD1 [561], TNF (tumor necrosis factor) [562], TNFRSF1B [563], APLNR (apelin receptor) [564], COMP (cartilage oligomeric matrix protein) [565], RETN (resistin) [566] and IGFBP1 [567] were associated with the progression of polycystic ovarian syndrome. Combined with the results of GO and REACTOME pathway enrichment analysis, these results imply these genes might participate in FSGS.…”
Section: Discussionmentioning
confidence: 99%